Pengaruh Organizational Culture Terhadap Kinerja Di Mediasi Komunikasi Interpersonal Pada Pegawai Badan Pendapatan Daerah Kabupaten Bengkalis - fadli agus; Richa Afriana Munthe; Siti Syamsudarmi (CV. Akira Java Bulu, 2025)
This study aims to determine the Analysis of the Influence of Organizational Culture on Performance through Interpersonal Communication of Employees of the Bengkalis Regency Regional Revenue Agency. The population in this study were all ASN employees of the Bengkalis Regency Regional Revenue Agency where the sampling was carried out using the saturated sample method so that the number of samples obtained was 57 respondents. The data collection technique used a questionnaire and distribution using a google form. The data analysis technique in this study was with Structural Equation Modeling (SEM) using SmartPLS 3.0 as a data processing tool. The results of this study indicate that organizational culture and interpersonal communication have a positive effect on employee performance, in addition, interpersonal communication is able to mediate the influence of organizational culture on the performance of Bengkalis Regency Regional Revenue Agency Employees.